β-carotene supplementation in non-forage diets in female breeding guinea pigs (Cavia porcellus) - Bustios M., Carla (2018)
The objective of the study was to evaluate the β-carotene supplementation in nonforage diets of female breeding guinea pigs. Experiment I was carried out in the spring (October-December) with 27 females at the first parturition and experiment II was carried out in the summer (January-April), with the same females during their second parturition. Three diets were evaluated: mixed (green forage + concentrated), integral (only concentrated) and integral + β-carotene. The supplementation of β-carotene did not improve the productive or reproductive parameters in guinea pigs in both experiments. The results of the second parturition were affected by the summer, showing the beneficial role of β-carotene as an antioxidant, natural or synthetic, in body weight of mothers at weaning.